Islamic bank assets management performance: an empirical evaluation / Mohd Affandi Abu Bakar, Abdul Malek A Tambi and Mohd Fauzi Mohd Harun - Abu Bakar, Mohd Affandi; A Tambi, Abdul Malek; Mohd Harun, Mohd Fauzi (Universiti Teknologi MARA, Perak, 2011)
This paper evaluates the performance of lslamic bank's assets management for the period of 1996 to 2008. The study also evaluates the impact of the interest rate movement on the Islamic bank's performance. To reflect the managerial efficiency, the study adopted the financial ratio approach. The study discovered that the Islamic banks on giving return to their shareholders and depositors are relatively indifference to conventional banks. In portfolio management, however, Islamic bank is less efficient compared with the conventional banks as shown by lower asset utilization and investment margin ratios. The Islamic bank investment margin fluctuates more than that of its counterpart during an upswing and downswing event of interest rate.